2009
DOI: 10.1111/j.1439-0469.1987.tb00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Comments on hexanchiform phylogeny (Pisces, Neoselachii)

Abstract: The Hexanchiformes (Cow Sharks) are regarded as a monophyletic taxon. Cladistic analysis shows that among the various neoselachian taxa proposed so far as the sister group of the Hexanchiformes a sister group relationship between the Hexanchiformes and a (still unnamed) taxon comprising the Squaliformes and Pristiophoriformes appears as the most probable hypothesis. In addition, MAISEY and WOLFRAM'S (1984) concept of hexanchiform interrelationships is critically reviewed. An alternative cladogram of hexanchifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In contrast, Thies (1987) and Maisey (1984) did not find characters to support hexanchiform monophyly, and Pfeil (1983) erected the order Chlamydoselachiformes for Chlamydoselachus based on external morphology, skeleton, and teeth, undoubtedly influenced by its many distinctive features. Furthermore, Chlamydoselachus and Hexanchidae were not united in the phylogenetic studies of Shirai (1992, 1996) and Carvalho and Maisey (1996; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Thies (1987) and Maisey (1984) did not find characters to support hexanchiform monophyly, and Pfeil (1983) erected the order Chlamydoselachiformes for Chlamydoselachus based on external morphology, skeleton, and teeth, undoubtedly influenced by its many distinctive features. Furthermore, Chlamydoselachus and Hexanchidae were not united in the phylogenetic studies of Shirai (1992, 1996) and Carvalho and Maisey (1996; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Another study (Soares & Carvalho, 2013b) of the morphology and subsequent description of the musculature associated with the jaws and the hyoid arch allowed a better understanding of the family Chlamydoselachidae, and its sole genus, Chlamydoselachus, previously included in the order Hexanchiformes. It was found that this family has no muscular characters in these arches that indicate a closer relationship of the family inside this order as found by previous authors that found this same arrangement based on other characters (Thies, 1987;Shirai, 1992). In another study, the same authors (Soares & Carvalho, 2013a), found evidence from the same muscles that reinforced the hypothesis that Orectolobiformes are the sister-group to Heterodontiformes within Galeomorphi, and not the sister-group of Lamniformes + Carcharhiniformes as previously advocated (Compagno, 1973, Thies & Reif, 1985.…”
Section: Musculature Associated With the Visceral Skeleton And Its Ussupporting
confidence: 83%
“…Echinorhiniformes being closely related to Hexanchiformes was previously suggested by Ridewood (1899), Varoujean (1972) and Pfeil (1983) based on the branchial skeleton, neurocranium, soft anatomy and dental characters. This was later rejected by Thies (1987) on a reevaluation of dental characters and by Bernardi and Powers (1992) employing molecular data, and recent phylogenetic hypothesis which included this order as a sister taxon of the remaining Squaliformes (Shirai and Nakaya, 1992; Carvalho, 1996; Shirai, 1996) or as a sister group of Squatiniformes + Pristiophoriformes (Naylor et al., 2012a) or of Squatiniformes only (Maisey et al., 2004; Heinicke et al., 2009). This current study proposes for the first time morphological synapomorphies supporting the sister relationship of Echinorhiniformes + Hexanchiformes.…”
Section: Discussionmentioning
confidence: 99%